Features of Russian Corporate Culture - Olga RUDAKOVA; Yury VASYUTIN; Tatyana TISHCHENKOVA; Nelly ORLOVA (Communications of International Proceedings, 2020)
As international cooperation has increased, problems related to the peculiarities of cross-cultural interaction are of importance. Significant differences between countries determine the relevance of studying the institute of corporate culture in Russia as an economic and socio-cultural phenomenon. According to domestic experts, the prerequisites for the formation of the institute of corporate culture in Russia emerged in the mid-1980s. Russian corporate culture is still being formed. Its rapid growth in our country is largely due to globalization and the desire of domestic corporations to become a part of the world economy. Russian researchers note that the formation of corporate culture in the country was influenced by and contains features of pre-revolutionary (pre-Soviet) corporate culture; the corporate culture of the Soviet period and contemporary foreign corporate culture. The research is aimed at analyzing the factors responsible for emergence of Russian corporate culture, identifying the stages of its development and defying its characteristics.
Keywords: Russian Corporate Culture; Soviet Corporate Culture; Pre-Revolutionary Corporate Culture; “Soft” Corporate Culture; “Hard” Corporate Culture; Leadership; Power.